Risk perception, knowledge, information sources and emotional states among COVID-19 patients in Wuhan, China: A cross-sectional survey (2020)
Background: The rapidly evolving COVID-19 pandemic has become a global health crisis. Several factors influencing risk perception have been identified, including knowledge of the disease, information sources, and emotional states. Prior studies on COVID-19-related risk perception primarily focused on the general public, with little data available on COVID-19 patients. Purpose: To investigate COVID-19 patients’ risk perception, knowledge of the disease, information sources, and emotional states in the epicenter, Wuhan, during the COVID-19 outbreak in China. Method: Data were collected online using self-administered electronic questionnaire developed with reference to previous relevant studies and publications by the World Health Organization. Findings: A higher level of perceived risk was found in relation to COVID-19 as compared to other potential health threats. Knowledge gaps existed regarding transmission and prevention of COVID19. Additionally, risk perception was negatively related to knowledge and positively related to depressive states. Moreover, social media was a primary source for COVID-19 information, whereas the most trusted sources were health professionals. Discussion: Realistic perception of risk should be encouraged considering both physical and mental health while developing relevant strategies. Furthermore, risk communication needs to be specifically tailored for various target groups, such as the elderly and mentally vulnerable individuals, with the adoption of popular media platforms.